ANALYSIS OF THE RELATIONSHIP BETWEEN RENAL REMODELING AND VASCULAR ADHESION-1 PROTEIN (VAP-1) IN CHRONIC PRIMARY GLOMERULONEPHRITIS - H. Z. Gadaborsheva; E. S. Levitskaya; M. M. Batiushin; N. V. Antipova; N. A. Bronovitskaya; E. A. Sinelnik; I. V. Sarvilina (SINAPS LLC, 2017)
Goal. Determination of the relationship between the concentration of VAP-1 and the clinical and morphological parameters of the structural reorganization of the renal tissue.Materials and methods. The study included 80 patients with primary chronic glomerulonephritis in the period of exacerbation. The predominant morphological variants were IgA-nephropathy (42 patients) and focal-segmental glomerulosclerosis (16 patients). All patients underwent general clinical examination, with the establishment of stages of CKD, and nephrobiopsy was performed. Based on the results of morphological analysis, the parameters of remodeling of renal tissue were taken into account. A blood sample was taken to study the concentration of Vascular Adhesion-1 protein (VAP-1). Nine months after the patients were admitted to the study and treated according to standard therapy, several indicators were re-recorded.Results. It was found that the age, duration of the disease, urea, proteinuria of a single and a daily portion of urine were inversely proportional to the level of VAP-1. Moreover, a signifi cant difference was found between the groups of patients ranked by median VAP-1, by prevalence in the group ofpatients with higher VAP-1 concentration of nephritic syndrome, IgA nephropathy, cases with mesangium expansion, mesangial and endothelial hypercellularity, endothelial swelling, IgA immune deposits In mesangium and capillary loops.Conclusion. As a result of the study, the prognostic signifi cance of VAP-1 concentration in patients with chronic glomerulonephritis was demonstrated. The formulas and the table of risk stratifi cation for the development of morphological reconstruction of kidney tissue are presented. It was found that the concentration of VAP-1 is statistically signifi cantly increased in the early stages of glomerulonephritis, with the predominance of infl ammatory and proliferative changes. At the stage of fi brous restructuring of renal tissue, there was no reliable difference. When analyzing the material obtained, it was concluded that it is necessary to determine the level of VAP-1 in patients with chronic glomerulonephritis, especially IgA-nephropathy, in the early stages of the disease, in order to predict its course.